Historical and biographical essay on the life and activity of academician G.O. Graftio - Mahobei, K. M. (History of science and technology, 2014)
The article focuses ontheli feandcareerof distin guished engineer late XIXth - early XXth Henry Osipovich Graftio. The features of the academician sactivity, thatallowedhimto winthede served reputationof world-classengineers, wasanalysed.